The Impact of Experimental Preconditioning Using Vascular Endothelial Growth Factor in Stroke and Subarachnoid Hemorrhage - Sven Oliver Eicker; Moritz Hoppe; Nima Etminan; Stephan Macht; Jason Perrin; Hans-Jakob Steiger; Daniel Hänggi (Stroke Research and Treatment)
Vascular endothelial growth factor (VEGF) stimulating angiogenesis was shown to be a potential novel therapeutic approach for the treatment of ischemic vascular diseases. The goal of the present study was to examine whether transfection of VEGF before occurrence of major stroke (part I) and cerebral vasospasm after experimental subarachnoid hemorrhage (SAH; part II) develops neuroprotective qualities. A total of 25 (part I) and 26 (part II) brains were analyzed, respectively. In part one, a significant reduction of infarct volume in the VEGF-treated stroke animals (43% reduction, P<0.05) could be detected. In part two, significant vasospasm was induced in all hemorrhage groups (P<0.02). Analyzing microperfusion, a significant higher amount of perfused vessels could be detected (P<0.01), whereas no significant effect could be detected towards macroperfusion. Histologically, no infarctions were observed in the VEGF-treated SAH group and the sham-operated group. Minor infarction in terms of vasospasm-induced small lesions could be detected in the control vector transduced group (P=0.05) and saline-treated group (P=0.09). The present study demonstrates the preconditioning impact of systemic intramuscular VEGF injection in animals after major stroke and induced severe vasospasm after SAH.